Hungarian Monitoring, 20 May 1989 . [Magyar rádiófigyelő], 1989. május 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reporting from the scene of events in Beijing - Demonstration held in Moscow to express sympathy with two parliamentary representatives - Komsomolskaya Pravda disapproves of Estonia's wish to introduce own currency - Arson on Red Square on May 1 Domestic Affairs: - First national talks held in Szeged by Hungarian Socialist Workers' Party (MSZMP) reform circles - Social Democratic Party of Hungary does not want to be a governing party for the time being - Report from discussions - Alliance of Young Democrats (Fidesz) leaves National Council of Trade Unions (SZOT) - National Peace Council in session - More recalls of parliamentary representatives in Budapest - Legal experts and historians prepare to re-examine 30,000 political trials - "168 Hours" interview with Vaclav Havel - Interview with Gyula Horn Economy: - Hungary the first socialist country to receive untied loan from Japan - Gabonatrüszt wound up Külpolitika: - Helyszíni beszámoló a Pekingben zajló eseményekről - Szimpátia tüntetés volt Moszkvában két parlamenti képviselő mellett - A Komszomolszkaja Pravda helyteleníti, hogy Észtországban saját valutát akarnak bevezetni - Május 1-én gyújtogatás volt a Vörös térnél Belpolitika: - Első országos tanácskozásukat tartják Szegeden az MSZMP reformkörei - A Magyarországi Szociáldemokrata Párt egyelőre nem akar kormányzó párt lenni - Tudósítás a tanácskozásról - A FIDESZ kilép a MISZOT-ból - Az Országos Béketanács ülése - Újabb parlamenti képviselő visszahívását kezdeményezték Budapesten - 3o ezer politikai per felülvizsgálatára készülnek a jogszakértők és a történészek - A 168 óra interjúja Václav Havellel - Horn Gyula interjú Gazdaság: - Japán a szocialista országok közül elsőként Magyarországnak nyújt kötetlen felhasználású pénzkölcsönt - Megszűnik a Gabonatröszt